Zirconia toughened alumina ceramic and its preparation method and application

CN122916625APending Publication Date: 2026-10-16HEBEI RUIHE MEDICAL DEVICES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611101680.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-07-06
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对现有技术中涂层预应力陶瓷存在的界面结合可靠性不足、热膨胀匹配困难、工艺复杂以及难以适配精密加工工件等问题,本发明提供一种氧化锆增韧氧化铝陶瓷及其制备方法和应用

Benefits of technology

[0035] This zirconia-toughened alumina ceramic surface layer possesses a residual compressive stress layer formed by an oxygen vacancy concentration gradient. This effectively inhibits the initiation and propagation of surface cracks, enhancing the material's flexural strength, fracture toughness, and resistance to surface damage, while maintaining the inherent high hardness, high wear resistance, and chemical stability of zirconia-toughened alumina ceramics. These performance characteristics make it suitable for applications with high requirements for surface mechanical properties and reliability, such as: as precision cutting tools, meeting the requirements for high hardness and high edge retention; as wear-resistant structural components and valves, providing a long service life under wear and erosion conditions; as grinding media, offering high wear resistance and low wear; and as biomedical ceramic components, maintaining surface integrity and mechanical reliability in long-term in vivo service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916625A_ABST
    Figure CN122916625A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high-performance structural ceramic materials, and discloses a zirconia toughened alumina ceramic as well as a preparation method and application thereof. The zirconia toughened alumina ceramic body is sintered under an oxygen-deficient atmosphere, oxygen vacancies are introduced into the ceramic matrix, the sintered body is subjected to annealing treatment in an oxygen-containing environment with an oxygen partial pressure of greater than or equal to 20 kPa, the ceramic surface layer oxygen vacancies are effectively supplemented, the internal oxygen vacancies are retained, the stable residual compressive stress layer is formed in situ on the ceramic body surface layer by means of the surface layer lattice expansion strain and the constraint effect of the internal matrix. The method can construct the prestress layer in situ on the ceramic body surface layer without adding a heterogeneous coating, avoids the problems of coating and matrix interface bonding, thermal expansion mismatch and coating peeling, and can significantly improve the bending strength of the zirconia toughened alumina ceramic, so that the zirconia toughened alumina ceramic has a wide application prospect in the fields of precision cutting tools, high-performance wear-resistant structural parts and biomedical ceramic parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance structural ceramic materials technology, and in particular to a zirconia-toughened alumina ceramic, its preparation method, and its application. Background Technology

[0002] Zirconia-toughened alumina ceramics, also known as ZTA ceramics, are typical two-phase composite ceramics with alumina as the main phase and zirconia as the toughening phase. ZTA ceramics combine the high hardness and high wear resistance of alumina ceramics with the phase transformation toughening properties of zirconia ceramics, and are currently widely used in precision cutting tools, high-performance wear-resistant parts, valves, grinding media, and biomedical artificial joint implants.

[0003] As the requirements for reliability and load-bearing capacity in structural ceramic applications continue to increase, further improving the flexural strength and surface crack resistance of ZTA ceramics has become an important direction for the research and development of this type of material. Existing methods for improving the strength of ZTA ceramics mainly include grain refinement strengthening, phase transformation toughening, second-phase bridging toughening, hot isostatic pressing densification, stabilizer ratio optimization, and multi-component additive regulation. These methods all achieve a synergistic improvement in strength and toughness from the intrinsic material level by controlling the overall microstructure, phase composition, or densification degree of the ceramic. However, flexural fracture in ceramic materials usually originates from the initiation and propagation of microcracks in the tensile region of the surface. The above methods are difficult to strengthen this core crack-prone area on the ceramic surface, thus having limited effect on improving the flexural strength of the material.

[0004] Introducing residual compressive stress into the ceramic surface is an effective technical approach to counteract surface tensile stress during service, hinder crack propagation, and improve the flexural strength of ceramics. Existing prestressed ceramic preparation methods often employ a heterogeneous composite approach, involving the application of low thermal expansion coefficient coatings, alumina reinforcement layers, or other heterogeneous composite layers to the ceramic substrate surface, followed by co-firing or post-treatment to induce compressive prestress on the surface. However, this type of coating or composite layer approach suffers from problems such as complex processes, the need for optimal coating materials, difficulty in controlling coating thickness uniformity, challenges in matching the thermal expansion coefficients of the coating and the substrate, insufficient interfacial bonding reliability, and the potential for interlayer cracking or peeling during long-term service. For ZTA ceramic workpieces that have already undergone precision machining, additional coating processes may alter the surface dimensions and roughness of the workpiece, compromising the original machining accuracy and failing to meet the stringent assembly precision requirements of high-end equipment applications.

[0005] Therefore, developing a preparation method that can form a stable residual compressive stress layer in situ on the surface of ZTA ceramic without the need for external heterogeneous coatings is of great technical significance and application value for simplifying the preparation process, eliminating the risk of heterogeneous interface failure, and further improving the flexural strength and service reliability of ZTA ceramics. Summary of the Invention

[0006] To address the problems of insufficient interfacial bonding reliability, difficulty in matching thermal expansion, complex processes, and difficulty in adapting to precision-machined workpieces in existing coated prestressed ceramics, this invention provides a zirconia-toughened alumina ceramic, its preparation method, and its application.

[0007] To achieve the above objectives, the present invention provides the following technical solution.

[0008] In a first aspect, the present invention provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: S1. The zirconia-toughened alumina ceramic preform is sintered in an oxygen-deficient atmosphere to obtain a sintered body with oxygen vacancies. S2. The sintered body is annealed in an oxygen-containing atmosphere to at least partially replenish the oxygen vacancies on the surface of the sintered body, forming a surface residual compressive stress layer to obtain zirconia toughened alumina ceramic. Wherein, the oxygen partial pressure of the oxygen-containing atmosphere is ≥20kPa.

[0009] Compared with the prior art, the method for preparing zirconia toughened alumina ceramics provided by the present invention first sintersects the ceramic in an oxygen-deficient atmosphere to form uniformly distributed oxygen vacancies inside the ceramic, and then performs annealing treatment in an oxygen-containing atmosphere to replenish the oxygen vacancies on the surface of the ceramic while retaining the internal oxygen vacancies, forming an oxygen vacancy concentration gradient from the surface to the interior. By utilizing the lattice expansion strain induced by the recovery of the surface lattice oxidation stoichiometry and the strong constraint effect of the matrix where no oxygen vacancy replenishment has occurred, a stable and controllable residual compressive stress layer is formed in situ on the surface and near-surface regions of the ceramic body.

[0010] This invention eliminates the need for additional heterogeneous coatings or composite layers throughout the entire process, fundamentally avoiding the inherent defects of traditional prestressed ceramic coating schemes, such as insufficient interfacial bonding reliability, susceptibility to interlayer cracking and peeling during long-term service, difficulty in controlling coating thickness uniformity, and complex process routes. It also does not alter the surface dimensions and surface roughness of the precision-machined workpiece, effectively ensuring the final assembly accuracy. Simultaneously, the in-situ formed residual compressive stress layer effectively offsets the surface tensile stress experienced by the ceramic during service, hindering the initiation and propagation of surface microcracks, significantly improving the flexural strength and surface crack resistance of zirconia-toughened alumina ceramics. Furthermore, this method offers strong process controllability, low implementation cost, and an integrated structure between the stress-reinforcing layer and the ceramic substrate, resulting in excellent service stability. It can well meet the performance requirements of high-reliability zirconia-toughened alumina ceramic components in high-end equipment, biomedical fields, and other areas.

[0011] Furthermore, in S1, the oxygen partial pressure of the oxygen-deficient atmosphere is lower than the oxygen partial pressure of the air atmosphere.

[0012] Furthermore, in S1, the oxygen partial pressure of the oxygen-deficient atmosphere is ≤1 Pa.

[0013] By further limiting the oxygen partial pressure of the oxygen-deficient atmosphere in step S1 to ≤1 Pa, a low oxygen partial pressure oxygen-deficient environment can be provided during sintering, allowing sufficient oxygen vacancies to form in the green body while densifying. The lower oxygen partial pressure facilitates the release of lattice oxygen into the atmosphere, resulting in a higher concentration and more uniform distribution of oxygen vacancies in the sintered body. This provides conditions for establishing an oxygen vacancy concentration gradient between the surface and interior during subsequent annealing, generating lattice expansion strain, and forming a residual compressive stress layer on the surface, thereby improving the strengthening effect of the ceramic surface.

[0014] Furthermore, in S1, the sintering temperature is 1400℃~1550℃, and the sintering time is 10min~4h.

[0015] Sintering under these conditions enables the green body to be fully densified, while the oxygen-deficient atmosphere effectively introduces oxygen vacancies. The aforementioned temperature range can balance the sintering driving force and grain growth control of zirconia-toughened alumina ceramics, avoiding insufficient density due to excessively low temperatures or abnormal grain growth due to excessively high temperatures.

[0016] Furthermore, the relative density of the sintered body obtained in S1 is greater than 98%. At this density, the ceramic matrix has been essentially densified with very few residual pores, which allows the intrinsic mechanical properties of zirconia-toughened alumina ceramics to be fully utilized.

[0017] Further, in S1, the sintering under an oxygen-deficient atmosphere includes one of vacuum pressureless sintering, vacuum hot pressing sintering, inert atmosphere sintering, hot isostatic pressing sintering, spark plasma sintering, oscillating hot pressing sintering, or microwave-assisted electric field sintering.

[0018] All of the above sintering methods can be used in step S1 to provide the oxygen-deficient atmosphere conditions, thereby achieving densification of the green body and the introduction of oxygen vacancies. In practice, one of the above sintering methods can be selected according to the size, shape, and production conditions of the target workpiece. All of them can effectively establish an oxygen vacancy base state in the sintered body while completing densification, providing a foundation for the formation of a surface residual compressive stress layer in subsequent annealing treatment.

[0019] Furthermore, prior to the annealing process described in step S2, the process further includes machining the sintered body into the shape of the target workpiece.

[0020] Specifically, the target workpiece shape is the shape of the final use state, or the shape of a standard spline used for bending strength testing.

[0021] Before the annealing process in step S2, the sintered body is first processed into the shape of the target workpiece. This allows the subsequent annealing process to be carried out in the final form of the workpiece, avoiding the removal or damage of the surface compressive stress layer that has already been formed due to machining when annealing is performed first and then processing.

[0022] Furthermore, in S2, the oxygen partial pressure of the oxygen-containing atmosphere is ≥21 kPa.

[0023] Annealing atmosphere has an oxygen partial pressure comparable to or higher than that of air, which can create a large oxygen partial pressure difference between the surface and interior of the sintered body. This provides a driving force for oxygen to diffuse from the surface to the near-surface layer and occupy oxygen vacancies, which is conducive to the full replenishment of oxygen vacancies on the surface, causing an increase in the surface lattice constant and resulting in lattice expansion. Meanwhile, the internal matrix does not expand synchronously, and the resulting constraint causes the surface lattice expansion to be converted into residual compressive stress, thereby forming a residual compressive stress layer on the surface of the target workpiece.

[0024] Furthermore, in S2, the annealing temperature is 900℃~1300℃, and the annealing time is 0.5h~8h.

[0025] Preferably, in S2, the annealing temperature is 900℃~1100℃, and the annealing time is 1h~2h.

[0026] Optimal annealing conditions can form a prestressed layer of moderate thickness on the ceramic surface, maximizing the prestressing strengthening effect. Excessive processing temperature or time will result in an overly thick prestressed layer, while low processing temperature or short time will result in an overly thin prestressed layer. Both excessively thick and thin prestressed layers will reduce the prestress formed within the layer.

[0027] In some specific embodiments of the present invention, the annealing treatment is carried out in an air atmosphere furnace, a muffle furnace purged with an oxygen atmosphere, or a tube furnace purged with an oxygen atmosphere. All of the above equipment are conventional heat treatment furnaces, offering good process controllability and ensuring that all parts of the workpiece surface are in full contact with oxygen during annealing, guaranteeing uniform replenishment of surface oxygen vacancies and forming a continuous and uniformly distributed residual compressive stress layer.

[0028] Furthermore, the zirconia-toughened alumina ceramic comprises an alumina main phase and a zirconia toughening phase; wherein the zirconia accounts for 10wt% to 30wt% of the total mass of the zirconia-toughened alumina ceramic.

[0029] Furthermore, the zirconia-toughened alumina ceramic also includes additives, which include at least one of yttrium oxide, strontium oxide, chromium oxide, magnesium oxide, or calcium oxide; wherein the total mass of the additives accounts for 0% to 5% of the total mass of the zirconia-toughened alumina ceramic.

[0030] To suppress the phase transformation of zirconia during cooling, yttrium oxide can also be included as a stabilizer. Furthermore, depending on the specific requirements of the product for color, hardness, toughness, and sintering performance, the ceramic may selectively include one or more additives selected from strontium oxide, chromium oxide, magnesium oxide, and calcium oxide. These additives can play roles in color adjustment, densification promotion, grain refinement, or second-phase strengthening during sintering. Their type and dosage are determined based on the target performance and do not affect the process effect of introducing oxygen vacancies during oxygen-deficient sintering and the formation of a residual compressive stress layer on the surface during subsequent annealing.

[0031] In some specific embodiments of the present invention, the mass fraction composition of the composite powder used in the zirconia-toughened alumina ceramic green body can be: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%. Al2O3 is the main matrix phase, providing the material with basic hardness, wear resistance, and chemical stability. ZrO2 is the toughening phase, dispersed in the alumina matrix in the form of a tetragonal phase, improving the fracture toughness of the material through a phase transformation toughening mechanism. Y2O3 acts as a stabilizer dissolved in the zirconia lattice, inhibiting the transformation of tetragonal zirconia to monoclinic phase during cooling, thus preserving the transformable tetragonal phase. HfO2 is a component associated with the zirconia raw material, and its chemical behavior is similar to that of zirconia, having no significant adverse effects on the material properties. SrO and Cr2O3 are additive components. SrO can promote sintering densification and regulate grain size, while Cr2O3 can play a role in color adjustment or forming solid solutions to improve hardness. After the above components are mixed and shaped to obtain a green body, and then subjected to oxygen-deficient atmosphere sintering and oxygen-containing annealing treatment as described in this invention, a zirconium oxide toughened alumina ceramic with a residual compressive stress layer on the surface can be obtained. Oxygen vacancies are retained inside, and the residual compressive stress on the surface is formed by lattice expansion strain induced by the oxygen vacancy concentration gradient.

[0032] Secondly, the present invention also provides a zirconia-toughened alumina ceramic, which is prepared by the method for preparing zirconia-toughened alumina ceramic described in any one of the above claims. The surface layer of the zirconia-toughened alumina ceramic has a residual compressive stress layer, which is formed by lattice expansion strain caused by the oxygen vacancy concentration on the surface being lower than that in the internal matrix.

[0033] Compared with conventional zirconia-toughened alumina ceramics, this ceramic has improved bending strength, fracture toughness and surface damage resistance due to the presence of a residual compressive stress layer on the surface, while maintaining the material's high hardness and wear resistance. It is suitable for applications with high requirements for surface mechanical properties and reliability.

[0034] Thirdly, the present invention also provides the application of the above-mentioned zirconia-toughened alumina ceramics in the preparation of precision cutting tools, wear-resistant structural parts, valves, grinding media or biomedical ceramic components.

[0035] This zirconia-toughened alumina ceramic surface layer possesses a residual compressive stress layer formed by an oxygen vacancy concentration gradient. This effectively inhibits the initiation and propagation of surface cracks, enhancing the material's flexural strength, fracture toughness, and resistance to surface damage, while maintaining the inherent high hardness, high wear resistance, and chemical stability of zirconia-toughened alumina ceramics. These performance characteristics make it suitable for applications with high requirements for surface mechanical properties and reliability, such as: as precision cutting tools, meeting the requirements for high hardness and high edge retention; as wear-resistant structural components and valves, providing a long service life under wear and erosion conditions; as grinding media, offering high wear resistance and low wear; and as biomedical ceramic components, maintaining surface integrity and mechanical reliability in long-term in vivo service environments.

[0036] In summary, this invention discloses a zirconia-toughened alumina ceramic and its preparation method. First, the zirconia-toughened alumina ceramic blank is sintered in an oxygen-deficient atmosphere to introduce uniformly distributed oxygen vacancies into the ceramic matrix. Then, the sintered body is annealed in an oxygen-containing environment with an oxygen partial pressure not lower than that of air, so that the oxygen vacancies on the ceramic surface are effectively replenished while the internal oxygen vacancies are retained. With the help of the surface lattice expansion strain and the constraint of the internal matrix, a stable residual compressive stress layer is formed in situ on the surface of the ceramic body. This preparation method eliminates the need for additional heterogeneous coatings, fundamentally avoiding the shortcomings of traditional coating-based prestressing schemes, such as insufficient interfacial bonding reliability, easy interlayer peeling, complex processes, and impact on workpiece machining accuracy. While retaining the high hardness and high wear resistance of the ceramic itself, it significantly improves the material's bending strength, fracture toughness, and surface crack resistance. Furthermore, it exhibits good process stability, is adaptable to various sintering methods and workpiece shapes, and is easy to industrialize. The resulting zirconia-toughened alumina ceramics can be widely used in precision cutting tools, high-performance wear-resistant structural components, industrial valves, and biomedical ceramic parts, demonstrating broad application prospects. Attached Figure Description

[0037] Figure 1 These are cross-sectional images of the zirconia-toughened alumina ceramics prepared in Examples 1-7 of this invention. Figure 2 This is a graph showing the relationship between the prestressed layer thickness and flexural strength of the zirconia-toughened alumina ceramics prepared in Examples 1-7 of this invention. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0039] To better illustrate the present invention, further examples are provided below.

[0040] The ZTA composite powder used in the examples is a commercially available product.

[0041] Example 1 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0042] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0043] The sintered body obtained above was processed into a standard bending resistance test specimen with dimensions of 3mm×4mm×36mm, and the surface of the specimen was polished. Subsequently, the processed specimen was placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.2 kPa, the annealing temperature was 1000℃, and the holding time was 1h. During the annealing process, oxygen atoms diffused from the surface of the specimen into the interior, replenishing the oxygen vacancies in the ceramic surface layer, forming an oxygen-compensated surface layer and inducing surface lattice expansion strain. After the surface lattice expansion strain was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface layer.

[0044] Three-point bending strength tests were conducted on the annealed specimens. The test span was 30 mm, the loading rate was 0.5 mm / min, and the number of samples in each group was no less than 5. The test results showed that the bending strength of the ZTA sintered body of the same batch that was only sintered and not annealed was 1280 ± 104 MPa; after air annealing at 1000℃ for 1 h, the bending strength of the sample increased to 1679 ± 78 MPa, an increase of approximately 31%.

[0045] Example 2 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0046] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0047] The sintered body obtained above was processed into standard bending resistance test specimens with dimensions of 3mm×4mm×36mm, and the surface of the specimens was polished. Subsequently, the processed specimens were placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.2 kPa, the annealing temperature was 900℃, and the holding time was 1 hour. During the annealing process, oxygen atoms diffused from the surface of the specimens to the interior, replenishing the oxygen vacancies on the ceramic surface, forming an oxygen-compensated surface layer and inducing lattice expansion strain on the surface. After the lattice expansion strain of the surface layer was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface.

[0048] After annealing, a shallow oxygen compensation layer appeared on the surface of the sample, with a depth of 28 μm. Three-point bending tests showed that after annealing at 900℃ for 1 hour, the flexural strength of the sample increased to 1461±91 MPa, representing a strength increase of approximately 14% compared to the sample that only underwent sintering without annealing. This example illustrates that short-time air annealing at 900℃ can also create surface prestress and improve strength, but the oxygen diffusion depth and compressive stress layer thickness are relatively small.

[0049] Example 3 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0050] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0051] The sintered body obtained above was processed into standard bending resistance test specimens with dimensions of 3mm×4mm×36mm, and the surface of the specimens was polished. Subsequently, the processed specimens were placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.2 kPa, the annealing temperature was 950℃, and the holding time was 1 h. During the annealing process, oxygen atoms diffused from the surface of the specimens to the interior, replenishing the oxygen vacancies on the ceramic surface, forming an oxygen-compensated surface layer and inducing lattice expansion strain on the surface. After the lattice expansion strain of the surface layer was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface.

[0052] After annealing, a shallow oxygen compensation layer appeared on the surface of the sample, with a depth of 45 μm. Three-point bending tests showed that after annealing at 950℃ for 1 hour, the flexural strength of the sample increased to 1528±36 MPa, representing an increase of approximately 19% compared to the sample that only underwent sintering without annealing. This example illustrates that as the annealing temperature increases, the degree of oxygen vacancy compensation on the surface increases, and the residual compressive stress layer enhances the improvement in flexural strength.

[0053] Example 4 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0054] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0055] The sintered body obtained above was processed into standard bending test specimens with dimensions of 3mm×4mm×36mm, and the surface of the specimens was polished. Subsequently, the processed specimens were placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.2 kPa, the annealing temperature was 1100℃, and the holding time was 1h. During the annealing process, oxygen atoms diffused from the surface of the specimens to the interior, replenishing the oxygen vacancies on the ceramic surface, forming an oxygen-compensated surface layer and inducing lattice expansion strain on the surface. After the lattice expansion strain of the surface layer was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface.

[0056] After annealing, a shallow oxygen compensation layer appeared on the surface of the sample, with a depth of 99 μm. Three-point bending tests showed that after annealing at 1100℃ for 1 hour, the flexural strength of the sample increased to 1423 ± 90.4 MPa, representing an increase of approximately 11% compared to the sample that only underwent sintering without annealing. This example illustrates that a significant strengthening effect can still be obtained at higher annealing temperatures, but the strength increase is slightly lower compared to the preferred treatment of 1000℃ for 1 hour.

[0057] Example 5 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0058] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0059] The sintered body obtained above was processed into standard bending resistance test specimens with dimensions of 3mm×4mm×36mm, and the surface of the specimens was polished. Subsequently, the processed specimens were placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.1 kPa, the annealing temperature was 1200℃, and the holding time was 1h. During the annealing process, oxygen atoms diffused from the surface of the specimens to the interior, replenishing the oxygen vacancies on the ceramic surface, forming an oxygen-compensated surface layer and inducing lattice expansion strain on the surface. After the lattice expansion strain of the surface layer was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface.

[0060] After annealing, a shallow oxygen compensation layer appeared on the surface of the sample, with a depth of 171 μm. Three-point bending tests showed that after annealing at 1200℃ for 1 hour, the flexural strength of the sample increased to 1371 ± 72 MPa, representing an increase of approximately 7% compared to the sample that only underwent sintering without annealing. This example illustrates that when the oxygen compensation layer is further deepened, the surface compressive stress layer still has a strengthening effect; however, due to the excessive depth of the oxygen compensation area, the stress gradient decreases, and the strengthening effect diminishes.

[0061] Example 6 This embodiment provides a method for preparing zirconia-toughened alumina ceramic, comprising the following steps: Using ZTA composite powder as raw material, the composition of the composite powder by mass fraction is: Al2O3 71.4%, ZrO2 25.5%, Y2O3 1.41%, HfO2 0.55%, SrO 0.75%, Cr2O3 0.28%.

[0062] The ZTA composite powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for sintering. The sintering temperature was 1550℃, the sintering pressure was 30MPa, and the holding time was 2h. During the sintering process, the oxygen partial pressure in the furnace was <1Pa. After sintering, a sintered body with oxygen vacancies was obtained.

[0063] The sintered body obtained above was processed into standard bending resistance test specimens with dimensions of 3mm×4mm×36mm, and the surface of the specimens was polished. Subsequently, the processed specimens were placed in an air atmosphere muffle furnace for annealing treatment. The oxygen partial pressure in the furnace was approximately 21.6 kPa, the annealing temperature was 1300℃, and the holding time was 1h. During the annealing process, oxygen atoms diffused from the surface of the specimens to the interior, replenishing the oxygen vacancies on the ceramic surface, forming an oxygen-compensated surface layer and inducing lattice expansion strain on the surface. After the lattice expansion strain of the surface layer was constrained by the insufficiently oxidized matrix inside, a residual compressive stress layer was formed in situ on the ceramic surface.

[0064] After annealing, a shallow oxygen compensation layer appeared on the surface of the sample, with a depth of 412 μm. Three-point bending tests showed that after annealing at 1300℃ for 1 hour, the flexural strength of the sample increased to 1324 ± 115 MPa, an increase of approximately 3% compared to the sample that only underwent sintering without annealing. This example illustrates that when the annealing temperature is too high, the oxygen compensation layer extends excessively inward, weakening the strain difference between the surface and the interior, thus reducing the residual compressive stress strengthening effect.

[0065] Example 7 The preparation process in this embodiment is basically the same as that in Example 1, except that the air atmosphere annealing temperature is fixed at 1000℃, the annealing holding time is adjusted, and four parallel tests are set up for 0.5h, 2h, 4h and 8h respectively to examine the effect of annealing time on the control effect of oxygen compensation layer depth and ceramic flexural strength.

[0066] Test results show that: when the annealing time is 0.5 h, the oxygen compensation layer depth on the sample surface is 43.9 μm, and the ceramic flexural strength is 1401 ± 51 MPa; when the annealing time is 2 h, the oxygen compensation layer depth is 89.2 μm, and the ceramic flexural strength is 1598 ± 44 MPa; when the annealing time is 4 h, the oxygen compensation layer depth is 117 μm, and the ceramic flexural strength is approximately 1402 ± 102 MPa; when the annealing time is 8 h, the oxygen compensation layer depth is 171 μm, and the ceramic flexural strength is 1372 ± 72 MPa. Cross-sectional images of the zirconia-toughened alumina ceramics prepared in Examples 1 to 7 are shown below. Figure 1 As shown.

[0067] The flexural strength test results of the zirconia-toughened alumina ceramics prepared in Examples 1 to 7 above are shown in Table 1 and... Figure 2 As shown.

[0068] Table 1 The oxygen compensation layer depth was determined using the following method: The annealed zirconia-toughened alumina ceramic sample was cut along its cross-section and polished, then observed under an optical microscope. Due to the replenishment of surface oxygen vacancies during annealing, the oxygen vacancy concentration decreased, causing the material color to lighten. The sample cross-section showed a clear boundary between a light-colored shell and a dark core. After taking a cross-sectional micrograph, the thickness of the light-colored shell was measured. This thickness represents the depth of the oxygen compensation layer, characterizing the extent of the residual compressive stress layer formed by the oxygen vacancy concentration gradient. The color change caused by the difference in oxygen vacancy concentration within the material itself allows for a direct and accurate determination of the oxygen compensation layer depth.

[0069] The test results from the above embodiments show that the annealing temperature and annealing time jointly determine the depth of the oxygen compensation layer on the ceramic surface. The depth of the oxygen compensation layer further affects the construction effect of the residual compressive stress layer on the surface and the improvement of the material's flexural strength. When the depth of the surface oxygen compensation layer is shallow, the effective residual compressive stress layer thickness is insufficient, the prestress formed by insufficient lattice expansion is small, and the strength improvement effect is insufficient. When the depth of the surface oxygen compensation layer is too large, the oxygen vacancy concentration gradient between the ceramic surface and the internal matrix decreases, the lattice strain gradient weakens accordingly, the constraint effect of the internal matrix on the surface expansion strain decreases, the residual compressive stress level decreases, which also leads to a reduction in the strengthening effect. Based on the above experimental patterns, the depth of the oxygen compensation layer formed by annealing is preferably controlled in the range of 40μm~100μm, more preferably about 60~90μm, at which point an excellent flexural strength improvement effect can be obtained.

[0070] Example 8 This embodiment is used to investigate the effect of different formulations of ZTA composite powder on improving flexural strength under the same annealing process, and to verify the universality of the method of the present invention on ZTA ceramic systems with different components. All samples were prepared using the same vacuum hot pressing sintering process as in Example 1: the corresponding formulation of composite powder was loaded into a graphite mold and held in a vacuum hot pressing sintering furnace at 1550℃ and 30MPa pressure for 2 hours, with an oxygen partial pressure <1Pa, to obtain a sintered body; the sintered body was processed into standard flexural test strips of 3mm×4mm×36mm and polished, then uniformly placed in an air atmosphere muffle furnace and annealed at 1000℃ for 1 hour. The three-point flexural strength and the thickness of the surface oxygen compensation layer of each sample before and after annealing were tested. The powder formulations and corresponding performance parameters of each group are shown in Table 2.

[0071] Table 2 Example 9 This embodiment is used to investigate the effect of different sintering processes on improving the flexural strength of ZTA ceramics under the same annealing process, and to verify the universality of the method of the present invention for various sintering methods. The ZTA composite powder formulation used in this embodiment is completely consistent with that in Example 1.

[0072] Dense ceramics were prepared for each group of samples using different oxygen-deficient sintering processes. During the sintering process, an oxygen-deficient environment with an oxygen partial pressure of <1 Pa was maintained to introduce uniformly distributed oxygen vacancies inside the ceramic matrix. The sintered bodies prepared by each sintering process were processed into standard bending test strips of 3mm×4mm×36mm and polished. They were then placed in an air atmosphere muffle furnace and annealed at 1000℃ for 1 hour. The three-point bending strength and the thickness of the surface oxygen compensation layer of each sample were tested before and after annealing. The sintering processes and corresponding performance parameters of each group are shown in Table 3.

[0073] Table 3 Comparative Example 1 ZTA composite powder (with the same composition as in Example 1) was vacuum hot-pressed and sintered according to the process parameters of Example 1. The oxygen partial pressure during sintering was <1 Pa, resulting in a sintered body. The sintered body was processed into standard flexural specimens of 3mm × 4mm × 36mm and polished. The standard specimens were then placed in a vacuum annealing furnace and annealed at 1000℃ for 1 hour under a vacuum environment with an oxygen partial pressure <1 Pa. Because the sintering and annealing processes were conducted in an oxygen-deficient atmosphere, the oxygen vacancy content inside the ceramic did not change significantly before and after annealing, failing to form an oxygen vacancy concentration gradient from the surface to the interior. Therefore, no oxygen compensation layer or residual compressive stress layer was constructed on the surface. Three-point bending strength tests showed that the bending strength of this group of samples remained essentially the same before and after annealing, approximately 1280 MPa, with no significant strength improvement.

[0074] Comparative Example 2 ZTA composite powder (with the same composition as in Example 1) was sintered at atmospheric pressure in an air atmosphere at a temperature of 1550℃ for 2 hours, with an oxygen partial pressure of approximately 21.2 kPa in the furnace, to obtain a sintered body. The sintered body was processed into standard bending test strips of 3 mm × 4 mm × 36 mm and polished. The standard test strips were then placed in an air atmosphere muffle furnace and annealed at 1000℃ for 1 hour. Because the sintering and annealing processes were conducted in an oxygen-containing atmosphere, the oxygen vacancy content in the ceramic matrix was extremely low during the sintering stage. The annealing process could not form a surface oxygen vacancy replenishment effect or a lattice strain gradient, thus no residual compressive stress layer was formed on the material surface. Three-point bending strength tests showed no significant change in the bending strength of this group of samples before and after annealing, both remaining at approximately 1220 MPa, indicating no improvement in strength.

[0075] The comparative results of the two sets above show that neither sintering nor annealing in a single atmosphere can form a residual compressive stress layer in situ on the surface of ZTA ceramics. It is necessary to pre-introduce uniform oxygen vacancies within the matrix through oxygen-deficient sintering, followed by oxygen-containing annealing to achieve directional replenishment of surface oxygen vacancies, forming an oxygen vacancy concentration gradient and a lattice strain gradient. Only then can a stable surface residual compressive stress layer be constructed with the help of the matrix constraint effect, resulting in a significant improvement in flexural strength.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing zirconia-toughened alumina ceramic, characterized in that, Includes the following steps: S1. The zirconia-toughened alumina ceramic preform is sintered in an oxygen-deficient atmosphere to obtain a sintered body with oxygen vacancies. S2. The sintered body is annealed in an oxygen-containing atmosphere to at least partially replenish the oxygen vacancies on the surface of the sintered body, forming a surface residual compressive stress layer to obtain zirconia toughened alumina ceramic. Wherein, the oxygen partial pressure of the oxygen-containing atmosphere is ≥20kPa.

2. The method for preparing zirconia-toughened alumina ceramic as described in claim 1, characterized in that, In S1, the oxygen partial pressure of the oxygen-deficient atmosphere is lower than that of the air atmosphere.

3. The method for preparing zirconia-toughened alumina ceramic as described in claim 1 or 2, characterized in that, In S1, the oxygen partial pressure of the oxygen-deficient atmosphere is ≤1 Pa; and / or In S1, the sintering temperature is 1400℃~1550℃, and the sintering time is 10min~4h.

4. The method for preparing zirconia-toughened alumina ceramic as described in claim 1, characterized in that, In S1, the sintering under an oxygen-deficient atmosphere includes one of the following: vacuum pressureless sintering, vacuum hot pressing sintering, inert atmosphere sintering, hot isostatic pressing sintering, spark plasma sintering, oscillating hot pressing sintering, or microwave-assisted electric field sintering.

5. The method for preparing zirconia-toughened alumina ceramic as described in claim 1, characterized in that, Before the annealing process described in step S2, the method further includes a step of processing the sintered body into the shape of the target workpiece.

6. The method for preparing zirconia-toughened alumina ceramic as described in claim 1 or 5, characterized in that, In S2, the annealing temperature is 900℃~1300℃, and the annealing time is 0.5h~8h.

7. The method for preparing zirconia-toughened alumina ceramic as described in claim 1, characterized in that, The zirconia-toughened alumina ceramic comprises an alumina main phase and a zirconia toughening phase; wherein the zirconia accounts for 10wt% to 30wt% of the total mass of the zirconia-toughened alumina ceramic.

8. The method for preparing zirconia-toughened alumina ceramic according to claim 1 or 7, characterized in that, The zirconia-toughened alumina ceramic further includes additives, which include at least one of yttrium oxide, strontium oxide, chromium oxide, magnesium oxide, or calcium oxide; wherein the total mass of the additives accounts for 0% to 5% of the total mass of the zirconia-toughened alumina ceramic.

9. A zirconia-toughened alumina ceramic, characterized in that, The zirconia-toughened alumina ceramic is prepared by the preparation method of any one of claims 1-8, wherein the surface layer of the zirconia-toughened alumina ceramic has a residual compressive stress layer, which is formed by lattice expansion strain caused by the oxygen vacancy concentration on the surface being lower than that in the internal matrix.

10. The application of the zirconia-toughened alumina ceramic of claim 9 in the preparation of precision cutting tools, wear-resistant structural parts, valves, grinding media or biomedical ceramic components.